International real estate economics - Tiwari, Piyush; White, Michael, 1965- (New York : Palgrave Macmillan, 2010)
"As the real estate market becomes increasingly international, it is essential to understand how specific national markets operate and relate to one another. The authors identify and explain the similarities and differences observed across different markets, providing a framework to explain how these diverse national markets converge"--Provided by publisher.
Machine generated contents note: PART 1: UNDERSTANDING INTERNATIONAL REAL ESTATE * Introduction * Theorising international real estate * PART 2: INTERNATIONAL REAL ESTATE MARKET ACTIVITY -- * International occupational real estate markets (CRE) * International real estate investment markets -- * International real estate development * International professional real estate services * PART 3: THE DEVELOPMENT OF INTERNATIONAL REAL ESTATE MARKETS * European real estate markets * North American real estate markets * Pacific-Asia real estate markets * Other market areas * PART 4: SUMMARY AND FUTURE DIRECTIONS * Towards an internationalised real estate market PART 1: UNDERSTANDING INTERNATIONAL REAL ESTATE * Introduction * Theorising international real estate * PART 2: INTERNATIONAL REAL ESTATE MARKET ACTIVITY -- * International occupational real estate markets (CRE) * International real estate investment markets -- * International real estate development * International professional real estate services * PART 3: THE DEVELOPMENT OF INTERNATIONAL REAL ESTATE MARKETS * European real estate markets * North American real estate markets * Pacific-Asia real estate markets * Other market areas * PART 4: SUMMARY AND FUTURE DIRECTIONS * Towards an internationalised real estate market.
Includes bibliographical references and index.
Keywords: Real estate investment; Real estate business; Real estate development